Implications of Climate Change for Fresh Groundwater Resources in Coastal Aquifers in Bangladesh - World Bank (World Bank, Dhaka, 2017)
The objective of this study is to improve understanding of the implications of climate change for the groundwater systems in coastal Bangladesh. This is achieved by: (a) obtaining available geologic, hydrologic, and geochemical information on coastal aquifers of Bangladesh; (b) developing groundwater flow and salt transport models representing general features and conditions along the coast of Bangladesh; and (c) simulating potential changes in the groundwater systems due to various aspects of human activity and climate change. The simulation analysis will focus on both the pattern and response time of the saltwater-freshwater distribution in subsurface aquifers, with a view towards sustainability of current and future water use under stress due to climate change. The study is aimed at understanding processes and rates of change for systems representative of a range of conditions in coastal Bangladesh, but it is expected that regional and local differences occur. Thus, only general conclusions and guidance should be drawn from this work.